An explicit finite-difference scheme for wave propagation in nonlinear optical structures - Al-Sunaidi, M. A. (2001)
In this paper, we present an algorithm that solves a time-domain nonlinear coupled system arising in nonlinear optics. The algorithm is an explicit nonlinear finite-difference method (NFDM) based on the exact solution of the nonlinear discrete equations. It enables simulations that preserve the characteristics of nonlinearity as well as coupling, and can be extended to arbitrary input waveform conditions.